The effects of early intervention on the speech of children with cleft palate: A preliminary study - Fatemeh Derakhshandeh; Fatemeh Mostajeran; Mahbubeh Nakhshab; Yalda Kazemi; Akbar Hasanzadeh (Vesnu Publications, 2013)
Introduction: Children with cleft palate have limited consonant inventories with compensatory articulation (CA) errors that are considered as the primary concern for this group of children because these errors can affect early language development. Early intervention (EI) is needed to increase normal speech production and to minimize the development of CAs. As there is no study on the effectiveness of EI for children with cleft palate in Iran, this study aimed at examining the impact of an early intervention, which involved focused stimulation method, on the speech of this group of children. Materials and Methods: This clinical trial study with single subject design targeted four children with cleft palate. Their language samples were collected before and after intervention and each time, were transcribed by two independent transcribers to obtain three speech measures, namely, percent consonant correct (PCC), percent of compensatory errors and consonant inventory. All children had compensatory errors in their speech. The intervention method was "focused stimulation" which was taught to the mothers. The mothers practiced this method with their children at home. The second set of language sampling was conducted two months after the first assessment. The inter-rater reliability showed a high correlation between two independent transcriptions in most measures. Results: As results indicated, the percent of correct consonant did not change by the intervention. No significant differences regarding the percent of compensatory errors were found in children before the initiation and after the termination of intervention in spite of some increases. Increase in consonant inventory was approximately significant. Conclusion: Although the changes were not significant after the intervention, children increase their consonant inventory and reduce their compensatory errors following the intervention. The findings of this study indicate that if this study replicated with a larger sample and/or with a longer period of intervention, it might lead to more significant changes. The results indicate that early intervention program in children with cleft palate may lead to improvement of speech and can prevent the establishment of compensatory errors. Keywords: Early intervention, Cleft palate, Speech, Focused stimulation